2014
DOI: 10.1186/1476-069x-13-25
|View full text |Cite|
|
Sign up to set email alerts
|

A round robin approach to the analysis of bisphenol a (BPA) in human blood samples

Abstract: BackgroundHuman exposure to bisphenol A (BPA) is ubiquitous, yet there are concerns about whether BPA can be measured in human blood. This Round Robin was designed to address this concern through three goals: 1) to identify collection materials, reagents and detection apparatuses that do not contribute BPA to serum; 2) to identify sensitive and precise methods to accurately measure unconjugated BPA (uBPA) and BPA-glucuronide (BPA-G), a metabolite, in serum; and 3) to evaluate whether inadvertent hydrolysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 87 publications
3
88
1
Order By: Relevance
“…As serum BPA in a relative low range is high enough to elicit biological effects through its related receptors, assessing serum BPA rather than urinary BPA is reasonable and should not be ignored [29,30]. On the other hand, BPA determined after enzymatic hydrolysis by a sensitive and selective liquid chromatography-tandem mass spectrometry method is thought to be the most accurate chemistry method [6]. A significant correlation (r ¼ 0.971) was confirmed between the BPA values measured by the ELISA and the high-performance liquid chromatography [31].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…As serum BPA in a relative low range is high enough to elicit biological effects through its related receptors, assessing serum BPA rather than urinary BPA is reasonable and should not be ignored [29,30]. On the other hand, BPA determined after enzymatic hydrolysis by a sensitive and selective liquid chromatography-tandem mass spectrometry method is thought to be the most accurate chemistry method [6]. A significant correlation (r ¼ 0.971) was confirmed between the BPA values measured by the ELISA and the high-performance liquid chromatography [31].…”
Section: Discussionmentioning
confidence: 98%
“…However, as circulating BPA is considered to be more directly related to its biological effects, measurement of circulating BPA is needed [6,29]. National Institute of Environmental Health Sciences has demonstrated that serum BPA can be accurately assayed [6]. As serum BPA in a relative low range is high enough to elicit biological effects through its related receptors, assessing serum BPA rather than urinary BPA is reasonable and should not be ignored [29,30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of samples must be carried out with fully validated analytical methods and supported by the use of quality control samples (Albertini et al, 2006;Calafat and Needham 2008;Smolders et al, 2009). Finally, the laboratory should participate in inter-laboratory exercise as and when available (Göen et al, 2012;Schindleret al, 2014;Vandenberg et al, 2014).…”
Section: General Considerations For Interpretation Of Human Biomonitomentioning
confidence: 99%